Plano de gestão sustentável dos resíduos na agroindústria canavieira em Sergipe - Cruz, Izaclaudia Santana da (2011)
The industry of sugar cane improvement represents a traditional sector and fundamental to Brazil’s economy, agribusiness is dedicated primarily to produce sugar and alcohol. In Sergipe, the improvement of sugar cane is one of the main economic activities, and production is concentrated in six sugar cane plants located in the state. It is known that during alcohol production and sugar, these industries also generate wastes which are of great economic importance, such as bagasse and vinasse. However these residues when they are destined improperly can cause environmental damage, so it is necessary to adopt waste management in order to meet the aspirations of sustainable development. This theme is of great importance once the issues relating to the reuse of waste occupy now a significant portion of investments by economic sectors, including sugar cane plants. In addition it includes to economic factors, social, cultural, political and environmental aspects. Based on the paper presents theoretical reference, a literature that demonstrates the importance of the sugar cane agro-industrial sector in the context of sustainable development, and address the Environmental Management System ISO 14001 and the main waste generated by the agroindustrial activity. The results showed that sergipanas sugar cane plants have not adopted yet the policy of managing its waste, aiming at sustainability. Therefore, the management plan developed in this work will be important to this industry segment in Sergipe perfect their waste management practices, contributing to environmental preservation.